Strengthening of substandard reinforced concrete beam-column joints by external post-tension rods. (15th January 2016) - Yurdakul, Özgür; Avşar, Özgür
Highlights: Efficacy of use of post-tensioning for retrofit of substandard joints is investigated. Retrofit technique substantiates the efficiency in the strength. Proposed retrofit strategy enhanced the response quantities of specimens considerably. Use of post tension with column back plate keeps the lateral strength equal in both direction. Proposed method postpones the crack propagation and concrete crushing in the joint. Abstract: The efficiency of the proposed strengthening method using externally applied post-tension rods in reinforced concrete external beam-column joints, which do not comply with any code requirements, is investigated. Five full-scale specimens were tested in the laboratory. They have specific deficiencies resulting from the lack of shear reinforcement in the joint and poor material properties including low strength concrete and the presence of plain round reinforcement bars. While all specimens were built with column and in plane beam, one of the tested specimens consists of a transverse beam to demonstrate the applicability of the presented retrofit technique. All specimens were subjected to a cyclic quasi-static loading up to 8% drift ratio to observe different levels of structural damage. Two post-tension rods, which were mounted diagonally at each side of the joint, are utilized as a local retrofit technique. The reference specimen displayed a brittle behavior with the concentration of shear cracks mostly in the joint while the rest of the RC components were almost in their elastic range. The ultimate lateral load capacity was increased considerably for all retrofitted specimens. However, a brittle type of failure mechanism was observed such as a joint shear failure or beam-joint failure in the three retrofitted specimens. A relatively ductile response was observed in the specimen with transverse beam, although the axial force in the post-tension rods was the same with the specimens without transverse beam. After testing all specimens, it is found that the lateral force capacities of the beam-column assemblies can be improved up to code requirements by the proposed retrofitting method.